Nonlinear buckling analysis of porous-core FG-GPLRC toroidal shell segments with generalized meridional curvature reinforced by orthogonal stiffeners - Nam, Vu Hoai; Huong, Kieu Lan; Ly, Le Ngoc; Doan, Cao Van; Hieu, Pham Thanh (Vietnam Journal of Mechanics, 2026)
By utilizing the Donnell shell theory with von Kármán strain-displacement relationship, the nonlinear buckling behavior of porous core functionally graded graphene platelet-reinforced composite (FG-GPLRC) toroidal shell segments with generalized meridional curvature reinforced by stiffeners subjected to external pressure is introduced in this paper. Orthogonal FG-GPLRC stiffeners are applied on the bottom surface to enhance the load-carrying capacity of the shells. An improved smeared stiffener technique is employed for the FG-GPLRC stiffeners, while a three-term solution form is selected to satisfy the simply supported boundary conditions. The Ritz method is used to determine the explicit expressions for the critical buckling load and the load-deflection postbuckling curve of the shells. Numerical results reveal that both the stiffener configuration and the porous core thickness significantly influence the critical and postbuckling loads. Additionally, the effects of graphene distribution and geometric parameters on the nonlinear buckling behavior of stiffened FG-GPLRC toroidal shell segments are analyzed in detail.